간장박의 휘발성 향기성분에 관한 연구 - 차용준(Yong-Jun Cha); 왕문봉(Wenfeng Wang); 차하람(Ha-Ram Cha) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2016)
Volatile flavor compounds in soy sauce residue (SSR) and acid hydrolysate of SSR (AHSSR) were analyzed by solid phase micro extraction (SPME)/gas chromatography (GC)/mass spectrometry (MSD) methods. A total of 79 compounds were detected in samples (66 SSR and 60 AHSSR). Quantitatively, alcohols (433.37 ng/g), aldehydes (273.01 ng/g), esters (236.80 ng/g), and aromatic hydrocarbons (180.66 ng/g) were dominant in the volatiles of SSR, whereas furans (249.27 ng/g) were only dominant in AHSSR (P<0.05). Among these, four esters, 3-methylbutyl acetate (banana/pear-like), ethyl 3-methyl butanoate (fruity), ethylbenzene acetate (wine-like), and ethyl 3-methyl butanoate (apple-like), three alcohols, 3-methyl-1-butanol (fruity/whisky-like), 2-phenylethanol (floral/sweet), and 1-octen-3-ol (mushroom-like), four aldehydes, (E)-2-phenyl-2-butenal (chocolate-like), benzaldehyde (almond-like), 3-methylbutanal (malty), and 2-phenylacetaldehyde (floral), four aromatic hydrocarbons, 4-ethyl-2-methoxyphenol (smoky/soy sauce-like), 4-ethylphenol (medicine-like), 4-vinyl-2-methoxyphenol (woody), and phenol (woody), and two furans, furfural (almond-like) and 4-hydroxy-2,5-dimethyl-3(2H)-furanone (caramel-like), were major compounds in SSR, whereas seven compounds, including furfural, 5-methylfurfural (almond-like), 3-methyl-1-butanol, 2-phenylethanol, 4-ethyl-2-methoxyphenol, 3-methylbutanal, and benzaldehyde were major compounds in AHSSR. 간장박 및 그 산가수분해물의 휘발성 향기성분을 SPME/GC/MSD 분석법으로 분석한 결과 총 79종의 화합물이 간장박(66종)과 산가수분해물(60종)에서 동정되었다. 에스테르 및 알코올류가 각각 15종으로 가장 많았고, 알데히드류 11종, 산류 9종, 방향족 화합물류 8종, 퓨란류 8종, 케톤류 7종 및 기타 화합물류 6종이었다. 함량 면에서는 간장박에서 알코올 함량(433.37 ng/g)이 가장 많았으며, 다음으로 알데히드류(273.01 ng/g), 에스테르류(236.80 ng/g) 및 방향족 화합물류(180.66 ng/g) 순이었다. 산가수분해물에서는 퓨란류가 249.27 ng/g으로 가장 많았으며(P<0.05), 알코올을 제외한 나머지 화합물류는 15 ng/g 미만이었다. 간장박에서는 4종의 에스테르류, 3-methylbutyl acetate(바나나/배향), ethyl 3-methyl butanoate(익은 과일향), ethylbenzene acetate(와인향), ethyl 3-methyl butanoate(사과향), 3종의 알코올류, 3-methyl-1-butanol(과일/위스키향), 2-phenylethanol(꽃/달콤한향), 1-octen-3-ol(버섯향), 4종의 알데히드류, (E)-2-phenyl-2-butenal(초코렛향), benzaldehyde(알몬드향), 3-methylbutanal(엿기름향), 2-phenylacetaldehyde(꽃향), 4종의 방향족 화합물류, 4-ethyl-2-methoxyphenol(연기향/간장향), 4-ethylphenol(약품향), 4-vinyl-2-methoxyphenol(나무향), phenol(나무향) 및 2종의 퓨란류, fufural(알몬드향), 4-hydroxy-2,5-dimethyl-3(2H)-furanone(카라멜향)이 지배적이었다. 반면에 산가수분해물에서는 furfural, 5-methylfurfural(알몬드향), 3-methyl-1-butanol, 2-phenylethanol, 4-ethyl-2-methoxyphenol, 3-methylbutanal, benzaldehyde 등의 화합물이 지배적이었다.